Theory of Light Hydrogenic Bound States - Eides, Michael I.; Grotch, Howard; Shelyuto, Valery A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The book describes the modern theory of light hydrogen-like systems, and the discussion is based on quantum electrodynamics. In particular, Green's functions, relativistic bound-state equations and Feynman diagrams are extensively used. New theoretical approaches are described and explained. The book contains derivation of many theoretical results obtained in recent years. A complete set of all theoretical results for the energy levels of hydrogen-like bound states, as well as comparison with experiment, is presented.
Theoretical Approaches to the Energy Levels of Loosely Bound Systems -- General Features of the Hydrogen Energy Levels -- External Field Approximation -- Essentially Two-Particle Recoil Corrections -- Radiative-Recoil Corrections -- Nuclear Size and Structure Corrections -- Lamb Shift in Light Muonic Atoms -- Physical Origin of the Hyperfine Splitting and the Main Nonrelativistic Contribution -- Nonrecoil Corrections to HFS -- Essentially Two-Body Corrections to HFS -- Hyperfine Splitting in Hydrogen -- Notes on Phenomenology.
Keywords: Physics; Nuclear physics; Atoms; Physics; Atomic, Molecular, Optical and Plasma Physics; Particle and Nuclear Physics; Electronic books